2020
DOI: 10.1111/bdi.12983
|View full text |Cite
|
Sign up to set email alerts
|

Lithium in drinking water and suicide prevention: The largest nationwide epidemiological study from Japan

Abstract: Objectives The aims of the present study thus were (a) to further investigate the association between lithium levels in drinking water and suicide rates by adjusting relevant factors using the so far largest available dataset in Japan, (b) to confirm sex differences, (c) to estimate the effects of long‐term exposure to trace lithium, (d) to investigate the effects of drinking bottled instead of tap water, and (e) to exploratorily investigate which lithium levels may be associated with lower suicide rates. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 22 publications
2
15
1
Order By: Relevance
“…Additionally, this necessitates further clinical studies to confirm the aforementioned findings. For example, in the association between suicide rate and lithium in drinking water, we performed clinical studies [2,3] to directly confirm the indirect evidence from epidemiological studies [27][28][29][30] although we could not perform RCTs for that field.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this necessitates further clinical studies to confirm the aforementioned findings. For example, in the association between suicide rate and lithium in drinking water, we performed clinical studies [2,3] to directly confirm the indirect evidence from epidemiological studies [27][28][29][30] although we could not perform RCTs for that field.…”
Section: Discussionmentioning
confidence: 99%
“…Most of natural bodies of water have higher Na content, which alleviates toxic Li effects (Kszos & Stewart, 2003;. Kugimiya et al (2020) reviewed the literature data and concluded that Li content in drinking water ranges from 0 to 219 µg/L depending on the location and environmental conditions. Li found in drinking water is completely bioavailable.…”
Section: ____________________________________________________________...mentioning
confidence: 99%
“…The potential minimum effective dose of lithium in preventing suicide should be examined. As a previous study showed that 30 µg/L or more lithium concentration in drinking water is associated with lower suicide rate [ 36 ], a certain minimum dose of lithium may be required to achieve anti-suicidal properties. Although several studies have examined the effect of micro-dose lithium on mood or cognitive impairment [ 26 , 27 , 37 ], no clinical trial has investigated the effect of micro-dose lithium on suicide.…”
Section: Discussionmentioning
confidence: 99%